2000
DOI: 10.1592/phco.20.19.1423.34854
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol and Seizures: A Surveillance Study in a Managed Care Population

Abstract: In a general population, risk of seizure may be associated with long-term therapy with tramadol or the presence of cofactors, or confined to a small sensitive population subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
4
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(91 citation statements)
references
References 22 publications
1
80
4
6
Order By: Relevance
“…Also, we found that seizure is not gender related and previously proposed relation to younger ages is questionable. These observations are inconsistent with some previous reports [25,26]. Blood tramadol concentration was much higher in males maybe because males are more prone to drug dependency, abuse, and tolerance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, we found that seizure is not gender related and previously proposed relation to younger ages is questionable. These observations are inconsistent with some previous reports [25,26]. Blood tramadol concentration was much higher in males maybe because males are more prone to drug dependency, abuse, and tolerance.…”
Section: Discussioncontrasting
confidence: 99%
“…Seizure occurred in almost one third of tramadol overdoses (135 out of 401), which is inconsistent with previous reports [5,9,25]; although lower prevalence of seizure has been reported [8,26]. In this study, the smallest reported dose associated with seizure was 200 mg (was seen in four patients).…”
Section: Discussioncontrasting
confidence: 99%
“…The high frequency of seizure (46.2%) in the present study is remarkably different from other studies [23,24]. Jick et al in 1998 found no increased risk of seizure upon use of tramadol alone [25], while Gardner et al found seizures in 1% of adult tramadol users after the first tramadol prescription [23]. In both studies, patients received tramadol at therapeutic doses.…”
Section: Discussioncontrasting
confidence: 90%
“…The lack of effect on the respiratory centre has also made tramadol by default, the 'weak opioid' of choice in paediatrics following the withdrawal of codeine [6]. However, it is also the serotoninergic and noradrenergic effects that give tramadol its most troublesome reported side-effects: sedation [7]; lowering of the convulsion threshold [8]; and delirium [9]. Tramadol is a racemic mixture of two enantiomers: (+)-tramadol and (À)-tramadol.…”
Section: Pharmacology Of Tramadolmentioning
confidence: 99%
“…The early studies [6][7][8] included fewer than 60 patients each, so were subject to sampling error, and were carried out during the era of highdose opioid anaesthesia. The later studies were prospective, used a balanced anaesthesia technique, and included 600-900 patients, finding an incidence of 0.3-1.14% [11][12][13].…”
mentioning
confidence: 99%